Demandas, desafios e limites do novo Ensino Médio: o que pensam profissionais da educação profissional - Lima, José Roberto (2019)
This dissertation seeks to identify and analyze new demands for school management arising from the implementation of the reform of the New High School, pointing challenges and limits in the perception of professionals from a vocational education school unit. The study historically contextualizes the scenario of Vocational Education in Brazil, the main guidelines of Law No. 13,415 / 17, which amended the Law of Guidelines and Bases of National Education and established changes in the structure of High School. Studies about the implementation of educational public policies that subsidize the analysis categories are also analyzed. The study, with a qualitative approach, researched in a State Technical School unit the motivations of its management team, to understand and interpret certain behaviors, opinion and expectations of individuals in a population. And finally, he makes an analysis, based on interviews with representatives in the unit in question and in the light of the specialized literature, bringing as a result of this analysis considerations on the importance of understanding, adherence, institutional environment and discretion. Regarding the comprehension, it was possible to affirm that there was the understanding of the management team, but the same did not happen with the teachers. The management team joined, but the teachers were suspicious of the implementation of the new law. About the institutional conditions and the discretion of the implementing agents was the action of the management team to avoid the reduction of the workload. As new demands for school management arising from the implementation of the reform of the New High School, it was identified the need to avoid reducing the workload of unit teachers, as well as the adequacy of unit hours. As challenges and limits in the perception of professionals of this professional education school unit, it was pointed out the need for a formative action about the New High School law, as well as the holding of debates around controversial points of the law and aspects related to the quality of life. education and the student's wishes and interests.